Stress and strain analysis of egg yolk separator - Abdul Malik, Norjasween; Mohammed Dzulhardy, Mohammed Khadzid Iman; Zainal Abidin, Nurrul Amilin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The design and fabrication of an egg yolk separator represent a significant advancement in kitchen utensils, aiming to streamline the process of separating egg yolks and whites efficiently. This project employs SolidWorks software for the design phase and subsequently fabricates and tests the designed egg yolk separator. The primary objectives include designing and fabricating a product capable of autonomously separating egg yolks and whites, thereby reducing the effort required by users during food preparation. The proposed egg yolk separator utilizes an ingenious design methodology. As the egg is broken directly over the starting point of the upper plane, it initiates a seamless process where the egg slides down. Gravitational force then comes into play, orchestrating the natural separation of the white egg from the yolk as they traverse through a strategically designed gap. This innovative approach ensures a simple yet effective means of egg yolk separation, enhancing the usability and efficiency of the proposed egg yolk separator. Additionally, this study will involve stress-strain analysis using SolidWorks to evaluate the structural integrity and performance of the egg yolk separator under different loading conditions. Integrating this analysis into the project will provide valuable insights into the performance and reliability of the product. By incorporating this methodology, the project aims to offer a promising solution to the challenges associated with traditional egg yolk separation methods, providing a user-friendly approach to streamline kitchen processes and improve overall productivity. As for conclusion, the egg yolk separator has been successfully designed and fabricated, hence mark a significant achievement in addressing the objectives of the project. The seamless operation and effectiveness of the separator underscore its potential to revolutionize egg yolk separation practices, contributing to enhanced efficiency and productivity in culinary environments.